Quality Improvement Project: Perioperative Care for Patients with Cardiac Implantable Electronic Devices - Mizell, Coley (My University, 2023)
With the number of patients requiring implantable cardiac devices continuing to rise each year, the demand for anesthesia providers to be knowledgeable on proper management during the perioperative period has become critically essential. Improper perioperative cardioverter-defibrillator management by Certified Registered Nurse Anesthetists has the potential to result in patient harm and could be costly for both the patient and facility. The current process for anesthesia providers delivering perioperative care for patients with CIEDs lacks standardization and creates the potential for unexecuted safety measures related to their devices. The purpose of this quality improvement project was to assess anesthesia providers’ perceptions of an AICD/PPM Handout as an educational tool to improve perioperative CIED management and patient safety. This quality improvement project was implemented in cardiovascular-designated operating rooms in a Level I trauma center in eastern North Carolina. Ten nurse anesthetists were sent an AICD/PPM Handout and introductory PowerPoint, along with pre- and post-intervention surveys. Respondents shared their perceptions on the inadequacy of awareness and utilization of current practice guidelines and hospital policy, the unnecessary time taken to attain patient device information, and the potential benefits educational guides could provide during the perioperative period. Survey results indicated that most CRNAs encounter problems in attaining pertinent device information, consuming unnecessary time, and that many CRNA’s are unaware of or don’t use the hospital’s policy or current practice guidelines. Using data collected from these surveys could provide guidance for future improvements in perioperative AICD/PPM management.
None
Keywords: cardiac implanted electronic devices, nurse anesthetists, perioperative, device management